Groundwater quality beneath an Asian megacity on a delta: Kolkata’s (Calcutta’s) disappearing arsenic and present manganese - McArthur, J.M.; Sikdar, P.K.; Leng, M.J.; Ghosal, U.; Sen, I. (ACS Publications, 2018)
Kolkata, the capital city of West Bengal, exploits groundwater for public water-supply. The groundwater has been reported to be widely polluted by arsenic (As). Analysis for As in 280 groundwaters from across Kolkata, failed to detect As concentrations >10 μg/L from natural processes. Arsenic concentrations between 10 and 79 μg/L found in 14 of the 280 groundwaters are remnant from a pollution-plume emanating from a single factory site where Paris Green, an arsenical pesticide, was manufactured between 1965 and 1985. In 45% of groundwaters sampled, concentrations of Mn exceed 0.4 mg/L, a putative health guideline value for drinking water. Sporadic minor hazards are posed by Pb > 10 μg/L introduced into groundwater from well-fittings, from 4% of groundwaters with F concentrations between 0.75 and 1 mg/L, and the 14% of groundwaters containing more than 500 mg/L Na, concentrations that might contribute to excessive daily intake of Na. Compounding hazards from As, F, Mn, Na, and Pb, shows that 64% of public wells and 40% of municipal wells supply groundwater of suspect quality. Groundwaters comply with WHO Guideline Values for drinking water in terms of Cr, Cu, Co, NO2, NO3, Sb, Se, and U. Aesthetic guideline values for Fe, Mn, SO4, and Cl are exceeded for many groundwaters.